The Iranian Jewish Community in Search of Modern Social Life, 1848–1906 - Nemati, Nourddin; Faizee, Cyrus; Advay, Mazhar (Folia Orientalia, 2026)
Powerful European countries in late 18th and early 19th centuries supported religious minorities and expanded missionaries’ activities, thus paving the way for social changes and evolutions. Having understood international circumstances and internal situations, Iranian Jews took influential and useful steps in changing social system. The Qajar Dynasty, in line with the demands of international Jew institutions, agreed with the establishment of new Jew institutions. The present paper tries to find an answer to this question: How did the Jews change their social system during the mentioned period? The paper hypothesis is that with the support of their international institutions as well as powerful European countries, the Jews urged Qajar Dynasty to provide a suitable background for the evolution of their social system.